2023
DOI: 10.1039/d3nj00460k
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 (P25) nanoparticle catalyzed C-alkylation and quinoline synthesis via the borrowing hydrogen method

Abstract: Creating new, environmentally friendly catalytic systems for producing C-C bonds from renewable feedstocks is a challenging objective in synthetic chemistry. Traditional methods often use expensive noble metals, organic or organometallic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…67 As expected, and in agreement with our EPR studies, we also observed an additional shoulder located at around 457.5 eV, attributed to Ti 3+ defects, while such a feature is almost absent or only a weak signal can be noticed in the case of P-25 which is as per the literature. 32,68 Furthermore, it can also be seen from Fig. 10 that the peaks of trivalent titanium in Yb-doped samples, viz.…”
Section: Resultsmentioning
confidence: 73%
“…67 As expected, and in agreement with our EPR studies, we also observed an additional shoulder located at around 457.5 eV, attributed to Ti 3+ defects, while such a feature is almost absent or only a weak signal can be noticed in the case of P-25 which is as per the literature. 32,68 Furthermore, it can also be seen from Fig. 10 that the peaks of trivalent titanium in Yb-doped samples, viz.…”
Section: Resultsmentioning
confidence: 73%
“…In 2023, several works were presented on the preparation of quinoline frameworks 53 from 2-aminobenzyl alcohols 1 and aryl ketones 8 in the presence of transition metal catalysts, such as Ru, [54] Ti, [55] and Ru/ FeÀ MgÀ Al hydrotalcite. [56] For instance, Samanta and co-workers developed an unprecedented synthesis of quinoline catalyzed by a novel cobalt(II) complex (Scheme 32).…”
Section: Metal-catalyzed Synthesis Of Quinolinesmentioning
confidence: 99%
“…[72] On the other hand, such features are absent or a very weak signal is noticed for P-25 at g = 1.999 and g = 1.971, respectively, for the presence of both anatase and rutile phases (see Figure 7b and 7c). [73] Further, quantitative analysis was performed using a standard procedure (Figure S11) so as to get the actual spin concentration in the samples under consideration, and the computed values are listed in Table 2. It can be seen from this table that the N-OMT samples show a significant amount of spin concentration, suggesting the presence of large amounts of Ti 3 + centres/intrinsic defects in the mesoporous titania matrix.…”
Section: Sem-edxmentioning
confidence: 99%